Separation of Bio-active Compounds and in vitro Antibacterial Potency of Callistemon linearis Floral Extract with Mechanism of Action - Das, Shubhaisi; Chandra, Goutam (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Infection caused by bacteria is treated with antibiotics which caused several side effects in human and animals. This problem enforced scientist to work out plant originated compounds for treatment of several disease caused by morbific bacteria. Objectives: Present work revealed isolation of bioactive phytocompounds from different fractions of Callistemon linearis flower ethanol extract by chromatographic technique and determination of their antibacterial potency against selected bacteria with mode of action in vitro. Materials and Methods: Antibacterial potency of four different fractions of ethanol extract were done quantitatively via Agar well diffusion method along with determination of Minimum Inhibitory Concentration, and Minimum Bactericidal Concentrations. Further, phytochemical analysis, Fourier Transform Infrared spectroscopic analysis, thin Layer Chromatography separation and Gas Chromatography Mass Spectroscopy analysis of bioactive fractions were done simultaneously to assess the presence of bioactive phytocompounds responsible for the antibacterial potency of the fractions. Time-kill assay, Nucleic acid and protein leakage assay, and FESEM study were employed to determine the mode of activity of the isolated active phytocompounds on the tested bacteria. Results: Maximum antibacterial activity was observed in NHEX of ethanol extract against Escherichia coli (MTCC 739). Chromatographic separation of NHEX detected several bioactive compounds. Assessment of Time-kill assay in treated and untreated bacterial strains determined that bioactive compound of NHEX was bactericidal in nature. Nucleic acid and protein leakage assay of bacterial cells with isolated active compound showed cell damages and FESEM images strongly ascertained this data. Conclusion: The C. linearis floral extract possesses antibacterial activities against selected pathogens and causes cellular damages.
Keywords: Callistemon linearis; Antibacterial activity; FT-IR; GC-MS analysis; Bioactive compounds; Mechanism of action